THE DYNAMICS OF EXPRESSION OF THE CARBOHYDRATE DETERMINANTS OF STRUCTURAL COMPONENTS OF MUCOUS MEMBRANE OF GLANDULAR ZONE OF HARD PALATE IN EXPERIMENTAL HYPOSALIVATION - Yeroshenko, G.A.; Tymoshenko, Yu.V. (World of Medicine and Biology, 2018)
The sounding of the hard palate mucosa by β-Gal specific peanut lectin (PNA) in the experimental hyposalivation has shown the suppression of marking intensity of the epithelial lamina layers during observation. The resident components of the connective tissue of the lamina propria (fibroblasts and collagen fibers) demonstrated the increase in the intensity of reactions from weak to moderate one. The persistent high-degree conjugation with galactose-specific receptors of mastocytes throughout the entire period of observation was noteworthy. The lowering of the binding specificity up to weak intensity of carbohydrate determinants’ exposure to peanut lectin on the basal membrane and plasmolemma (strong in the intact group, very strong on the 14th day of the observation) was established in the acini. The expression of myoepithelial receptors reduced from very strong to weak in the intact group. The study of the specificity with the receptors on the structural components of the basal membrane and basal plasmolemma of the excretory ducts of submandibular glands has revealed a weak reaction in the intact rats, which was increasing to strong one on the 14th day of the experiment, though it demonstrated a weak reaction on day 30 of the observation.